TAHAP PERKEMBANGAN ANAK (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Early childhood development does not always evolve according to the stages of his age. There aresome of them who are experiencing barriers to development such as developmental delay the child'smotor and language development if it does not get the stimulus optimally from the environment. Thisstudy was conducted to determine the factors that affect early childhood development. The researchwas conducted with cross sectional design using a quantitative approach. Study subjects a total of 29early childhood. The subject is taken by means of simple random sampling. Interviews andobservations were conducted to get primary data about variables under study. The independentVariable in this study is the characteristics and the role of the mother, characteristics and the role ofthe father, characteristics and role of caregivers, the characteristics and the role of peers,characteristics and the role of the means of play. The conclusion that can be drawn is that childrenwho did not get the role of a stimulus is optimal from the mother and the means to play the risky lbihhigh experience a less than optimal development.Keywords: child Development, parenting, the environment.